A One Health Evaluation of the University of Copenhagen Research Centre for Control of Antibiotic Resistance - Léger, Anaïs; Stärk, Katharina D.C.; Rushton, Jonathan; Nielsen, Liza R. (Frontiers in Veterinary Science, 2018)
We applied the evaluation framework developed by the EU COST Action “Network of Evaluation of One Health” (NEOH) to assess the operations, supporting infrastructures and outcomes of a research consortium “University of Copenhagen Research Centre for Control of Antibiotic Resistance” (UC-CARE). This 4-year research project was a One Health (OH) initiative with participants from 14 departments over four faculties as well as stakeholders from industry and health authorities aiming to produce new knowledge to reduce the development of antimicrobial resistance (AMR). This was a case study focusing on assessing beneficial and counter-productive characteristics that could affect the OH outcomes. The study was also used to provide feedback to NEOH about the evaluation framework. The framework and evaluation tools are described in the introduction paper of this special journal issue. Data for the evaluation were extracted from the funding research proposal, the mid-term UC-CARE project evaluation report and supplemented with opinions elicited from project participants and stakeholders. Here, we describe the underlying system, theory of change behind the initiative and adapted questions from the NEOH tools that we used for semi-open interviews with consortium members throughout the evaluation process. An online survey was used to obtain information from stakeholders. The NEOH evaluation tools were then used for the qualitative and quantitative evaluation of the OH characteristics of UC-CARE. Senior UC-CARE researchers were interested and willing to be interviewed. Young scientists were more difficult to engage in interviews, and only 25% of stakeholders answered the online survey. Interviewees mentioned that the main benefit of UC-CARE was an increased awareness and general understanding of AMR issues. All interviewees stated that the adopted OH approach was relevant given the complexity of AMR. However, some questioned the applicability, and identified potentially counter-productive issues mainly related to the information sharing, collaboration and working methods across the consortium. It was mentioned that a dedicated OH coordinator and a more integrated project organization would have allowed for more knowledge exchange, potentially leading to a higher societal impact.